Investigation on glass/epoxy composite surfaces machined by abrasive water jet machining - Mohd Azhari, Mohd Azmir; Khan, Ahsan Ali (Elsevier BV, 2008)
Experimental investigations were conducted to assess the influence of abrasive water jet machining (AWJM) process parameters on surface roughness (Ra) of glass fibre reinforced epoxy composites. The approach was based on Taguchi's method and analysis of variance (ANOVA) to optimize the AWJM process parameters for effective machining. It was found that the type of abrasive materials, hydraulic pressure, standoff distance and traverse rate were the significant control factors and the cutting orientation was the insignificant control factor in controlling the Ra. For noise factors effect, the forms of glass fibres and thickness of composite laminate showed the greatest influence on Ra. A Mathematical model was developed using piecewise linear regression analysis to predict the performance of Ra in terms of the cutting parameters of AWJM. The models successfully predicted the Ra of an AWJ machined glass/epoxy laminate within the limit of this study. Verification of the improvement in the quality characteristics has been made through confirmation test with respect to the chosen reference parameter setting. It was confirmed that the determined optimum combination of AWJM parameters satisfy the real need for machining of glass fibre reinforced epoxy composites in practice.